Pengaruh Citra Merek, Kelengkapan Produk dan Customer Experience Terhadap Keputusan Pembelian di UD.Bumi Pertiwi - Erry Adnyani, Ni Nyoman (LPPM Universitas Buana Perjuangan Karawang, 2023)
The purpose of conducting this research is to determine the effect of Brand Image,Product Completeness and Customer Experience on Purchasing Decisions at UD.Bumi Pertiwi. In this study using a quantitative approach. Data collection techniquesin this study used a questionnaire with a Likert scale. The number of samples usedin this study were 100 respondents. The sample selection used purposivesampling method, namely this method is sampling using certain considerations inaccordance with the desired criteria to be able to determine the number of samples tobe studied. The data analysis technique used in this research is SPSS. The resultsshowed that Brand Image, Product Completeness and Customer Experience had asignificant positive effect on Purchasing Decisions at UD. Bumi Pertiwi